Technical Efficiency of Independent Oil Palm Smallholder In Indonesia - Varina, Firna; Hartoyo, Sri; Kusnadi, Nunung; Rifin, Amzul (Jurnal Ekonomi Kuantitatif Terapan; 2021: Vol. 14, No. 1, Februari 2021 (pp.1-241), 2021)
This study assesses technical efficiency and possible sources of inefficiency of independent smallholder oil palm production in Indonesia with stochastic frontier approach.  The result show all the input variables is  positively affect the oil palm production and exhibit decreasing returns to scale .  The farmers have mean technical efficiency (TE) values 0.6541, however about 53 % farmers have TE above 0.70. Factors such as age of farmer, education, extension services, member of farmer group,  land ownership and funding sources have a positive and significant effect on technical efficiency. It is suggested that by improving factors such as input used, education level, technical assistance on farming practice and accessibility to credit facilities should be increase the productivity and technical efficiency of oil palm production.  The farmers who have plant over 30 years old, which the TE and productivity are the lowest values,  should be thinking about replanting